A Comparative Study of Pioneer Entry Decisions in the United States and China1. Issue 5 (27th November 2013) - Zhao, Y. Lisa; Song, Michael; Parry, Mark E.
<x xml:space="preserve">Abstract</x> According to the resource‐based view of the firm, competitive advantages arise from control and deployment of productive resources that are rare and difficult to imitate. Through early entry, pioneers can gain preferential access to key resources. However, the value of that access depends on the presence of isolating mechanisms that limit or prevent competitive imitation. Isolating mechanisms increase the desirability of early entry by lengthening the time horizon over which the firm can earn Ricardian rents on those resources. To explore these implications of the resource‐based view, this study examines the impact of isolating mechanisms on pioneer advantages by analyzing the market entry timing decisions of 209 U.S. and 302 Chinese entrepreneurs. We hypothesize that the stronger intellectual property and legal protections available in the United States are an isolating mechanism that should increase the perceived importance of differentiation and cost advantages in the United States relative to China. Consistent with this argument, we find evidence that the relationships between the number of successful first‐mover decisions and (1) perceived pioneer differentiation advantages and (2) perceived cost advantages are relatively stronger in the United States than in China. We also argue that the importance of personal relationships in China constitutes an isolating mechanism that should increase the perceived importance of preemptive pioneer advantages in China relative to the United States. Consistent with this reasoning, we find that the coefficient linking perceptions of pioneer preemptive advantages with the number of successful first‐mover decisions is significant in the Chinese sample and not in the U.S. sample, but the difference between these coefficients is not significant. These results provide support for the argument that the availability of strong IP and legal protection encourages early entry decisions by entrepreneurs because these protections enhance the pioneer's ability to build a differentiated position in the minds of target customers and secure a cost advantage over later entrants. The results also support the argument that strong personal connections and the practice of reciprocity play a key role in the success of Chinese entrepreneurs.